The association of shift work and coronary heart disease risk factors among male factory workers in Kota Bharu, Kelantan - Shafei, Mohd Nazri (2005)
INTRODUCTION: Modern society is changing quite rapidly in terms of economic, social and hUinan behaviour. Consequently, various types of work schedules have been applied by organizations and companies. Working hours are extended to evenings and nights, as well as on weekends. Shift work is one of the work hour systems in which a relay of employees extends the period of production beyond the conventional 8-hour working day. It potentially disrupts workers' normal biological or social diurnal rhythms or both. Shift work has been found to be associated with various health problems and there is a concern that shift workers are at higher risk to develop risk factors for coronary heart disease (CHD) such as hypertension, hypercholesterolaemia, obesity and diabetes mellitus (DM). OBJECTIVES: The study was undertaken to examine relationships between shift work and CHD risk factors, narnely high blood pressure (BP), dyslipidaemia (either hypercholesterolaemia, hyper-low density lipoprotein-cholesterolaernia, hypo-high density lipoprotein-cholesterolaernia or hypertriglyceridaernia), high body rnass index (BMI), diabetes mellitus and physical inactivity among rnale factory workers in a factory in Kota Bharu, Kelantan. METHODS: This study was a cross-sectional study of 76 shift and 72 day workers from a factory in Kota Bharu, Kelantan. Data was collected through a questionnaire on psychosocial and life-style factors. Anthropornetric and blood pressure rneasurement,fasting blood sugar and fasting lipid profiles analyses were obtained. Chi-square test was used to determine the significant difference in the prevalence for each CHD risk factors between the two worker groups. Multiple logistic regression was used to evaluate the odds ratio for each CHD risk factors associated with shifi work. RESULTS: The prevalence of high BP, hypercholesterolaemia, hypertriglyceridaemia and body mass index (BMI) of equal to or more than 25 kg/m2 were significantly higher among shift workers compared to day workers. There was no difference in the prevalence of dtabetes mellitus, hypo-high-density lipoprotein-cholesterolaemia, hyperhigh- density lipoprotein-cholesterolaemia and physical inactivity. When the shift workers were compared with the day workers, the adjusted odds ratio (OR) for high BP, BMI of equal to or more than 25 kg/m2 and physical inactivity were 9.1 (95% Cl 1.4- 56.8), 2. 9 (95% CI 1.3-6.1) and 7. 7 (95o/o Cl 2.1-27 .5) respectively. There was neither association of shift work with dyslipidaetnia, nor with diabetes mellitus. CONCLUSIONS: There were positive association between shifl work and high BP, BMI of equal to or tnore than 25 kg/m2 and physical inactivity which denotes a higher risk ofCHD risk factors among shifl workers compared to day workers.